Multiple pterygium syndrome: evolution of the phenotype. - Thompson, E M (1987)
The clinical features of the multiple pterygium syndrome are multiple congenital joint contractures, multiple skin webs, camptodactyly, vertebral anomalies, short stature, ptosis, and antimongoloid eye slant. We present 11 new cases to show the evolution of the full phenotype from birth and to confirm autosomal recessive inheritance. We emphasise morbidity secondary to respiratory impairment and that conductive deafness may be part of the syndrome.